REACHING SDG TARGET 14.4 BY ESTABLISHING PROVISIONAL ARRANGEMENTS FOR LAW ENFORCEMENT OPERATION - Ramon, Adrianus Adityo Vito (Faculty of Law, Parahyangan Catholic University, 2024)
The research article argues that establishing provisional arrangements for law enforcement operations in overlapping maritime claims areas could be a viable option for claimant states to suppress illegal, unreported, and unregulated fishing (IUUF), which hinders progress toward achieving Sustainable Development Goal (SDG) Target 14.4. This target emphasizes sustainable fishing practices, marine life protection, and effective fish population management, aiming to prevent overfishing, reduce harmful fishing techniques, and ensure the sustainability of fish stocks. Under the 1982 UN Convention on the Law of the Sea, provisional arrangements for law enforcement operations can provide a practical framework for claimant states to conduct joint efforts, pending and without prejudice to the final resolution of overlapping maritime claims. To substantiate this argument, the article employs a juridical normative legal research method to: analyze the connection between SDG Target 14.4 and IUUF, which may impede progress toward the goal; examine the challenges of enforcing laws in overlapping maritime claims areas, including the factors contributing to IUUF in such contexts; and assess the potential impact of provisional arrangements for law enforcement on suppressing IUUF and advancing the achievement of SDG Target 14.4. The study highlights that these arrangements could serve as a collaborative interim solution, promoting sustainable development and marine ecosystem conservation while territorial disputes remain unresolved.